Evaluation of dietary acid-binding capacity and butyrate-based feed ingredients on nursery pig performance and intestinal health parameters - Stas, Ethan Bradley (My University, 2024)
The 5 chapters of this dissertation involve 1) determining the effects of low acid-binding capacity (ABC) specialty soy protein sources on nursery pig performance in a commercial environment, 2) evaluating dietary ABC level on nursery pig performance and fecal dry matter (DM), 3) determining the effects of dietary acidifiers and other low ABC formulation strategies on nursery pig growth performance and fecal DM, 4) determining the effects of butyrate-based feed ingredient supplementation on nursery pig performance, fecal DM, serum chemistry, and intestinal short chain fatty acid concentration, and 5) a review to feeding wheat and wheat co-products to swine. Chapter 1 consisted of 2 experiments which used 3,317 weanling pigs to evaluate low ABC soy protein sources. In Exp. 1, low ABC soy proteins were used to replace animal protein sources. In Exp. 2, two specialty soy protein sources were used to formulate low and high acid-binding capacity at a pH of 4 (ABC-4) diets with or without pharmacological levels of Zn from ZnO. Results suggest that low ABC soy protein sources can replace animal protein sources and be used to achieve low ABC-4 diets to improve nursery pig performance and provide a similar response to pharmacological levels of Zn. Chapter 2 consisted of 2 experiments which used 660 weanling pigs to evaluate the optimal ABC-4 level of the diet. In Exp. 1, pigs were fed increasing ABC-4 levels in diets not containing pharmacological levels of Zn from ZnO plus a high ABC-4 diet with ZnO. In Exp. 2, pigs were fed increasing ABC-4 levels with two intermediate ABC-4 levels to determine if the strategy to change ABC-4 of the diet affects the response. Results suggest that the optimal ABC-4 level for nursery pig diets is 200 meq/kg from d 0 to 10 post-weaning and 250 meq/kg from d 10 to 24 post-weaning. Chapter 3 consisted of 2 experiments which used 1,025 weanling pigs to evaluate dietary acidifiers and other low ABC-4 formulation strategies on pig performance. In Exp. 1, pigs were fed four low ABC-4 diets that were formulated using four different dietary acidifiers and two high ABC-4 diets with or without added ZnO. In Exp. 2, pigs were fed three low ABC-4 diets that were formulated using an acidifier with an additional low ABC-4 formulation strategy plus two high ABC-4 diets with or without added ZnO. Results suggest that the use of different dietary acidifiers and formulation strategies to target a low ABC-4 level can affect the response in nursery pigs, but overall, low ABC-4 diet formulation improves pig performance compared to high ABC-4 diets without ZnO. Chapter 4 consisted of 2 experiments which used 2,538 weaned pigs to evaluate butyrate-based feed ingredients. In Exp. 1, pigs were fed a positive control containing feed-grade medications and pharmacological levels of Zn and Cu, a negative control diet without pharmacological Zn and Cu, and four different butyrate-based feed additives. In Exp. 2, pigs were fed a control diet, 4 different mono-tributyrin blends, and a commercial feed additive. The results suggest that mono-tributyrin blends can improve feed efficiency, fecal DM, cecal butyrate concentration, and hematological components in nursery pigs. Chapter 5 consisted of a literature review on feeding wheat and wheat co-products to swine. Overall, wheat can offer opportunities in swine diets because of its high crude protein, amino acid, and phosphorus content relative to other cereal grains. Additionally, wheat co-products vary in their nutrient concentration due to the amount of bran, germ, and endosperm that is added back to the co-product which can ultimately affect its application in swine diets.
Keywords: Nursery pig; Acid-binding capacity; Fecal dry matter; Acidifiers; Butyrate; Serum chemistry